Mental rotation abilities of gymnasts and soccer players: a comparison of egocentric and object-based transformations. An exploratory and preliminary study - Klotzbier, Thomas Jürgen; Schott, Nadja (Frontiers in Psychology, 2024)
Background and Objectives. The experience obtained from motor expertise may contribute to and enhance the development of particular visuo-spatial abilities.Motor expertise is an essential part of visual perception. This exploratory and preliminary study compares the response times of a mental rotation task with egocentric and object-based transformation instructions between soccer players of varying performance levels and gymnasts. Methods. Fifty-six male participants (all male) participated in the study and were grouped based on their sports experience. Soccer-specific novices (SS-N: n = 19; age = 15.9 ± 0.87), soccer-specific experts (SS-E: n = 17; age = 16.4 ± 0.70), gymnastic-specific experts (GS-E: n = 10; age = 16.6 ± 1.71), and gymnastic-specific novices (GS-N: n = 10; age = 16.0 ± 1.63) were recruited to perform a perceptual task (recognition of soccer-specific poses) and mental rotation tasks with different stimuli (soccer-specific poses, cubes, line-drawings of hands, letters). Results. During the perceptual task with instructions on egocentric transformation and soccer-specific poses, we observed that gymnasts had longer response times than soccer players. Our findings also suggest that experts correctly identified most of the poses in terms of accuracy. In the mental rotation task with object-based transformation, gymnasts processed all stimuli, even the soccer-specific poses, more accurately than both soccer groups. Conclusions. Our results suggest that gymnasts' motor expertise plays a role in their performance on mental rotation tasks involving both egocentric and object-based transformations, regardless of the stimuli presented.